THE BUDGET SOURCES OF FUNDING FOR THE SUPPORT OF MOTHERHOOD AND CHILDHOOD IN RUSSIA - O. Makhalina (Publishing House of the State University of Management, 2018)
A brief analysis of various trends in the development of the demographic situation has been provided in the article. The difficult current situation in Russia associated with the level of fertility and reproduction of the population has been examined. The causes of the demographic problem in Russia have been designated. The issues related to improving the welfare of Russian families, support for motherhood and childhood, the development of systems of various methods and tools of assistance, both in material and non-material form have been considered. The budget sources and the size of support for motherhood and childhood from various budgets of the budget system of the Russian Federation have been analysed.